Attenuated Salmonella potentiate PD-L1 blockade immunotherapy in a preclinical model of colorectal cancer - Al-Saafeen, Besan H.; Al-Sbiei, Ashraf; Bashir, Ghada; Mohamed, Yassir A.; Masad, Razan J.; Fernandez-Cabezudo, Maria J.; al-Ramadi, Basel K. (Frontiers in Immunology, 2022)
The use of immune checkpoint inhibitors to treat cancer resulted in unprecedented and durable clinical benefits. However, the response rate among patients remains rather modest. Previous work from our laboratory demonstrated the efficacy of using attenuated bacteria as immunomodulatory anti-cancer agents. The current study investigated the potential of utilizing a low dose of attenuated Salmonella typhimurium to enhance the efficacy of PD-L1 blockade in a poorly immunogenic model of colon cancer. The response of MC38 tumors to treatment with PD-L1 monoclonal antibody (mAb) was variable, with only 30% of the mice being responsive. Combined treatment with PD-L1 mAb and Salmonella resulted in 75% inhibition of tumor growth in 100% of animals. Mechanistically, the enhanced response correlated with a decrease in the percentage of tumor-associated granulocytic cells, upregulation in MHC class II expression by intratumoral macrophages and an increase in tumor infiltration by effector T cells. Collectively, these alterations resulted in improved anti-tumor effector responses and increased apoptosis within the tumor. Thus, our study demonstrates that a novel combination treatment utilizing attenuated Salmonella and PD-L1 mAb could improve the outcome of immunotherapy in poorly immunogenic tumors.